Application of Response Surface Methodology to Enhance Phenol Removal from Refinery Wastewater by Microwave Process. (28th April 2014) - Younis, Sherif A.; El-Azab, Waleed I.; El-Gendy, Nour Sh.; Aziz, Shuokr Qarani; Moustafa, Yasser M.; Aziz, Hamidi Abdul; Amr, Salem S. Abu
Abstract : Phenol contaminated petroleum refinery wastewater presents a great threat on water resources safety. This study investigates the effect of microwave irradiation on removal of different concentrations of phenol in an attempt for petroleum refinery wastewater treatment. The obtained results show that the MW output power and irradiation time have a significant positive effect on the removal efficiency of phenol. The kinetic reaction is significantly affected by initial MW output power and initial phenol concentrations. Response surface methodology (RSM) was employed to optimize and study the interaction effects of process parameters: MW output power, irradiation time, salinity, pH, and H2 O2 concentration using central composite design (CCD). From the CCD design matrix, a quadratic model was considered as an ultimate model (R 2 = 0.75) and its adequacy was justified through analysis of variance (ANOVA). The overall reaction rates were significantly enhanced in the combined MW/H2 O2 system as proved by RSM. The optimum values for the design parameters of the MW/H2 O2 process were evaluated giving predicted phenol removal percentage of 72.90% through RSM by differential approximation and were confirmed by experimental phenol removal of 75.70% in a batch experiment at optimum conditions of 439 W MW power, irradiation time of 24.22 min, salinity of 574 mg/L, pH 5.10, and initial H2 O2 concentration of 10% (v/v).